Evaluation and characterization of triticale silage (x. Triticosecale wittmack) to replace Sorghum bicolor (L.) Moench (S. Vulgare Pers.) silage as feed for beef cattle - Henz, Éderson Luis; Das Dores Ferreira Da Silva, Leandro; Bumbieris Junior, Valter Harry; Massaro Junior, Fernando Luiz; Zanin, Ediane; Gonçalves De Arruda, Maria Carolina [UNESP] (Universidade Estadual de Londrina, 2020)
The objective of this study was to evaluate the nutritional quality of silages containing 0, 25, 50, 75 and 100% triticale replacing sorghum silage feed for beef cattle. It was carried out fractionation of carbohydrates and proteins, and the parameters of ruminal degradation kinetics estimated by semiautomatic in vitro method of cumulative gas production of the silages. The experimental design completely randomized with five treatments and four replicates. Sorghum silage has less non-fibrous carbohydrates, and its substitution may explain the linear increase in the composition of fractions A and B1. In general, the proportions of fractions “A” and “B1 + B2” demonstrated that as sorghum replaced by triticale, the abundance of high availability proteins increased, as did the abundance of rapidly degradable proteins in the rumen. The final volume of gases produced by the fermentation of non-fibrous carbohydrates presented a negative linear relationship with increased triticale silage (P = 0.0001), while the degradation rates presented a positive linear relationship (P = 0.0001). Thus, there was rapid release of energy and nitrogen, which may meet the needs of microorganisms. Therefore, triticale silage can be substituted for sorghum silage in cattle feed as an excellent source of protein and energy without altering nutritional parameters.
Keywords: Food assessment; Gas production; Rate of degradation; Ruminant